Melacak Daya Jalar Neoliberalisme Global, Penderitaan Sebagai Basis Etis Pembangunan dan Opsi Pengembangan Masyarakat Versi Gereja Katolik - Benediktus Denar (STIPAS St. Sirilus Ruteng, 2020)
This paper aims to show controversy surrounding development. Therefore, there are two basic ideas that will be used by the author in this paper. First, the author rejects the theoretical framework and dominant paradigm in the study of development, power and poverty which places neoliberal capitalism as the main weapon used by the power to carry out development in order to reduce poverty. Second, the author will demonstrate an alternative development model which essentially places suffering as the main proposition of development. Here development is seen as a way of liberating people from suffering. Thus, the concept of liberating people from suffering is an inspiration used by the author to show Christian vision of development